Health behaviors and problems in Polish homeless men - Repka, Bernadetta; Bejda, Grzegorz; Kułak-Bejda, Agnieszka; Czarnecki, Damian; Ziółkowski, Marcin; Mosiołek, Anna; Szulc, Agata; Waszkiewicz, Napoleon; Ślifirczyk, Anna; Kułak, Wojciech; Krajewska-Kułak, Elżbieta (Frontiers in Public Health, 2023)
Introduction: Homelessness is considered to be a global problem, independent of the material situation of a given country and occurring in most societies around the world. Aim of the study: Assessment of the preferred health behaviours of homeless people. Material and methods: The study covered 153 men who are homeless and 312 men who are not homeless. The original questionnaire of homeless, and validated the Satisfaction with Life Scale (SWLS), the Health Behaviour Inventory (HBI), the General Self-Efficacy Scale (GSES) and the Multidimensional Health Locus of Control (MHLC) Scale were used. The research covered fully completed questionnaires from 153 homeless men staying in Białystok and Gdańsk homeless centers. Results On average, the homeless men assessed their health at 6.0±2.7 points, and the non-homeless at 7.8±2.2 points. (p <0.001). Significant differences were found between people experiencing a homelessness crisis and the control group in selected aspects concerning the everyday life hygiene of the respondents, health self-assessment, declarations of visits to a specialist and carrying out check-ups, level of satisfaction with life, coping with difficult situations, preferred pro-health behaviours and dimensions of health control. In the used scales, SWLS, HBI, GES, and MHCL, the majority of homeless men obtained average scores. They were rather dissatisfied with their lives, with a low level of effectiveness in coping with difficult situations and obstacles, a low level of health behaviours, and in the scope of health, control increasing the impact of chance. Conclusions:. The level of the presented health behaviours showed statistically significant diversification with all dimensions of the health locus of control, and its internal dimension with age, homelessness phase, the respondents' criminal history, being under constant medical care, and self-assessment of health.